New records of the cicada genus Fidicinoides Boulard and Martinelli, 1996 (Hemiptera: Cicadidae: Fidicinini) from the state of Mato Grosso, Brazil - Maccagnan, Douglas Henrique Bottura; Martinelli, Nilza Maria [UNESP]; Pereira, Nirélcio Aparecido [UNESP]; Neto, Sinval Silveira (My University, 2012)
Fidicinoides picea (Walker, 1850) and Fidicinoides poulaini Boulard and Martinelli, 1996 are recorded for the first time from the state of Mato Grosso, extending the known distribution of these species to the south. Thereby, the number of Fidicinoides species from Mato Grosso is increased to nine, being Mato Grosso the state with the largest number of recorded species of this genus in Brazil. © 2012 Check List and Authors.
Keywords: Cicada; Cicadidae; Hemiptera; Picea